In vitro activity of combinations of zinc chelators with amphotericin B and posaconazole against six Mucorales species - Leonardelli, Florencia (2019)
Mucormycosis is an emerging disease with high mortality rates. Few antifungal drugs are active against Mucorales. Considering the low efficacy of monotherapy, combination-therapy strategies have been described. It is known that fungi are susceptible to zinc deprivation, so we tested the in vitro effect of the zinc chelators clioquinol, phenanthroline, and N,N,N=,N=-tetrakis(2-pyridylmethyl)ethane-1,2-diamine combined with amphotericin B or posaconazole against 25 strains of Mucorales. Clioquinol-posaconazole was the most active combination, although results were strain dependent.